Voters’ perceptions of the policy making and performance of the elected government after 2018 general election in Pakistan - Ashraf, Mujeeba; Tahir, Muzamal (Frontiers in Political Science, 2024)
In this study, the phenomenological approach was used to explore the perceptions of Pakistan Tahreek Insaf (PTI) voters regarding PTI policy making and performance six months after the Pakistani general election of 2018 (GE-2018). The sample comprised 20 PTI voters, and data was collected through one-to-one interview. The thematic analysis led to the following broad and sub themes: The first broad theme, pre-election party ideology, was described by the following sub-themes: vision of change, fight against corruption, and developing Pakistan along the lines of the State of Medina. The second broad theme, the performance of the elected government, was understood through the following sub-themes: accountability, political stability, poor policy making, and false election pledges. And the last broad theme, the public’s perceptions of the future performance of the elected government can be explained by its single sub-theme, i.e., giving the elected government a chance to complete its tenure of five years. It can be concluded that most of the participants were optimistic that the elected government of Pakistan would fulfill its pre-election promises.